Investigation of First-year Learning Experiences in a Rural University in South Africa (Journal of Student Affairs in Africa, 2021)
This study investigated the first-year experiences (FYE) of students in a South African university. Survey research design was used in the study. The quantitative method was used for data collection and 1 479 first-year students were randomly selected. The findings reveal that first-year students in the selected South African rural-based university experience certain specific challenges amongst which are poor orientation to the new context, poor knowledge of the Higher Education system, and poor educational background of parents. The study recommends that a special office under the direct line management of the dean of students be established to observe and closely monitor the progress of first-year students. This office would accommodate orientation of first years, and liaise and collaborate with appropriate offices within the institution to ensure that first-year students are properly guided and assisted in integrating without stress into the university system.
Keywords: first‑year experience; orientation; placement; South Africa